ON A NEW SPECIES DIPYLIDIUM NANDEDENSIS SP. NOV. (EUCESTODA : DIPYLIDIDAE) FROM CAT FELIS DOMESTICUS FROM NANDED, INDIA - SHINDE, G. B.; PAWAR, S. B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Dipyllidium nandedensis sp. nov. from intestine of Felis domesticus from Nanded differs from all known species and comes closer to D. oerleyi, D. crassum and D. halli in number of testes (110 - 115) but it differs distinctly in shape of scolex, number and rows of hooks, number of testes, shape of cirrus pouch, position of ovary and shape, and position of vitelline gland.